2020
DOI: 10.1515/tjb-2018-0307
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity and nephrotoxicity following long-term prenatal exposure of paracetamol in the neonatal rat: is betaine protective?

Abstract: BackgroundParacetamol is one of the widely used antipyretic and analgesic drug around the world. Many researchers showed that paracetamol caused to hepatotoxicity or nephrotoxicity.ObjectiveIn the present study, we aimed to determine whether betaine has protective effects on hepatotoxicity and nephrotoxicity in neonate rats, following to long term maternal paracetamol exposure.Materials and methodsRandomly chosen neonates, from the neonate pools, were divided into three groups; Control (n=13), APAP (n=13), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…[ 21,61 ] ArE and XO have been reported to act as free radical scavengers. [ 21,62 ] The present work indicates that AChE, LDH, and XO activities considerably increased, whereas ArE and CA activities remarkably dropped in GalN given rats. An alteration of AChE, ArE, CA, and LDH and XO activities of brain and cerebellum tissues of the GalN group seems to be a cellular response to excessive formation of free radicals.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…[ 21,61 ] ArE and XO have been reported to act as free radical scavengers. [ 21,62 ] The present work indicates that AChE, LDH, and XO activities considerably increased, whereas ArE and CA activities remarkably dropped in GalN given rats. An alteration of AChE, ArE, CA, and LDH and XO activities of brain and cerebellum tissues of the GalN group seems to be a cellular response to excessive formation of free radicals.…”
Section: Discussionsupporting
confidence: 50%
“…[21,61] ArE and XO have been reported to act as free radical scavengers. [21,62] cerebellum tissues of the GalN group seems to be a cellular response to excessive formation of free radicals. In a study examining the relationship between oxidative stress and neurodegenerative disease multiple sclerosis), the changes in oxidative stress markers (increased TOS and decreased TAS levels) were associated with a decrease in ArE activities.…”
Section: Discussionmentioning
confidence: 99%
“…Betaine functions as a provider of methyl groups for the conversion of homocysteine to methionine in a metabolic process facilitated by betaine-homocysteine methyltransferase (BHMT). Studies have demonstrated that administering betaine to rats increases the levels of hepatic methionine and S-adenosylmethionine via inducing BHMT [74]. GSH is a crucial chemical that is created based on this pathway and serves as a notable endogenous antioxidant.…”
Section: Control Ratsmentioning
confidence: 99%
“…The antioxidant property of betaine is also evident from its protective effects against myocardial infarction induced in male albino rats (Ganesan et al, 2010). Betaine also exerts protective effects against hepatotoxicity and oxidative damage by regulating oxidative stress (Jiang et al, 2019;Özkoç et al, 2020).…”
Section: Organic Osmolyte Betaine Mitigates the Deleterious Effects O...mentioning
confidence: 99%